Contrary trends of grout consumption and water absorption at Sardasht - Mohammad Hassan Nazari; Ali Aalianvari; Mohamed El Tani (Scientific Reports)
Abstract A new interpretation of contrary trends of water absorption rate and cement mix consumption in rock grouting is presented. The classical interpretation is either a higher consumption due to fracturing or a higher absorption due to thin fractures that cannot be grouted. Higher grout consumption will depend on the distribution of fractures, their openings and extensions. This is proven by a time simulation of grouting data recorded at Sardasht dam. The simulation is made considering analytic tools and a spreadsheet with computation capabilities. The first step is to prove that the rock has been permeated and the second step is to differentiate the causes of consumption. The minimal flow criterion is integrated to the investigation and is necessary to define a frame for the comparison. Over consumption happens when ignoring the relation between the target and closure.